Proteomics, functional characterization and antivenom neutralization of the venom of Pakistani Russell's viper ( Daboia russelii ) from the wild - Faisal, Tasnim; Tan, Kae Yi; Sim, Si Mui; Quraishi, Naeem H.; Tan, Nget Hong; Tan, Choo Hock (Elsevier, 2018)
The venom proteome of wild Pakistani Russell's viper (Daboia russelii) was investigated through nano-ESI-LCMS/MS of the reverse-phase HPLC fractions. A total of 54 venom proteins were identified and clustered into 11 protein families. Phospholipase A2 (PLA2, 63.8%) and Kunitz-type serine protease inhibitor (KSPI, 16.0%) were most abundant, followed by snake venom serine protease (SVSP, 5.5%, mainly Factor V activating enzyme), vascular endothelial growth factor (VEGF, 4.3%), snake venom metalloproteinase (SVMP, 2.5%, mainly Factor X activating enzyme) and phosphodiesterase (PDE, 2.5%). Other minor proteins include cysteine-rich secretory protein (CRiSP), snake venom C-type lectin/lectin-like protein (snaclec), nerve growth factor, L-amino acid oxidase and 5′-nucleotidase. PLA2, KSPI, SVSP, snaclec and SVMP are hemotoxic proteins in the venom. The study indicated substantial venom variation in D. russelii venoms of different locales, including 3 Pakistani specimens kept in the USA. The venom exhibited potent procoagulant activity on human plasma (minimum clotting dose = 14.5 ng/ml) and high lethality (rodent LD50 = 0.19 μg/g) but lacked hemorrhagic effect locally. The Indian VINS Polyvalent Antivenom bound the venom immunologically in a concentration-dependent manner. It moderately neutralized the venom procoagulant and lethal effects (normalized potency against lethality = 2.7 mg venom neutralized per g antivenom). Biological significance: Comprehensive venom proteomes of D. russelii from different locales will facilitate better understanding of the geographical variability of the venom in both qualitative and quantitative terms. This is essential to provide scientific basis for the interpretation of differences in the clinical presentation of Russell's viper envenomation. The study revealed a unique venom proteome of the Pakistani D. russelii from the wild (Indus Delta), in which PLA2 predominated (~60% of total venom proteins). The finding unveiled remarkable differences in the venom compositions between the wild (present study) and the captive specimens reported previously. The integration of toxicity tests enabled the correlation of the venom proteome with the envenoming pathophysiology, where the venom showed potent lethality mediated through coagulopathic activity. The Indian VINS Polyvalent Antivenom (VPAV) showed binding activity toward the venom protein antigens; however the immunorecognition of small proteins and PLA2-dominating fractions was low to moderate. Consistently, the antivenom neutralized the toxicity of the wild Pakistani Russell's viper venom at moderate efficacies. Our results suggest that it may be possible to enhance the Indian antivenom potency against the Pakistani viper venom by the inclusion of venoms from a wider geographical range including that from Pakistan into the immunogen formulation.